A journey down the Tuin: the hydraulics of an internal draining river from the Khangai Mountains to the Gobi Desert - Fassnacht, Steven R., author; Venable, Niah B. H., author; Odgarav, Jigjsuren, author; Sukhbaatar, Jaminkhuyag, author; Adyabadam, Gelegpil, author; Nutag Action and Research Institute, publisher (Colorado State University. Libraries, 2015)
River systems flowing through semi-arid and arid regions provide critical ecosystem services for inhabitants of these areas. In remote and/or difficult to access areas away from population centers, few direct measurements exist to characterize the nature of streamflow in these systems. The Tuin River flows from the rugged high mountain and forest steppe landscape of the Khangai Mountains in central Mongolia to its terminus at Orog Lake in the desert steppe and sand dunes of the northern Gobi Desert. Field measurements taken in June 2012 at numerous locations from river headwaters to mouth were used to characterize streamflow in the main river channel and associated floodplain. From these measurements, channel hydraulic characteristics were estimated and hydrologic properties were assessed using a digital elevation model and other spatial data. These properties include contributing area, slope, hydraulic radius, and channel roughness. During the low flow conditions of the survey, streamflow was decreasing from upstream to downstream. At a point between the Bayankhongor and Bogd gaging stations, streamflow ceased at the surface and reappeared approximately 10 kilometres downstream, exemplifying losing flow conditions and subsurface flow components. The results of this analysis could be scalable to other internally draining river systems, especially for hydrologic modelling.
Presented at the Building resilience of Mongolian rangelands: a trans-disciplinary research conference held on June 9-10, 2015 in Ulaanbaatar, Mongolia.
Keywords: streamflow; hydrology; digital elevation model